SMALL AND MEDIUM ENTERPRISES - SCOPE OF MEDIA FINANCING IN INDIA - Oak, Amit Padmakar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the Indian context, the small and medium enterprises (SME) sector is broadly a term used for small scale industrial (SSI) units and medium-scale industrial units. Any industrial unit with a total investment in its fixed assets or leased assets or hire-purchase asset of up to Rs 10 million, can be considered as an SSI unit and any investment of up to Rs 100 million can be termed as a medium unit. An SSI unit should neither be a subsidiary of any other industrial unit nor be owned or controlled by any other industrial unit.